Pengaruh Intensitas Modal, Financial Distress, Insentif Pajak dan Risiko Litigasi terhadap Konservatisme Akuntansi Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2020 - kristina, dian; Yuniarta, Gede Adi (Universitas Pendidikan Ganesha, 2021)
This study was aimed at finding out the effect of (1) capital intensity on accounting conservatism, (2) financial distress on accounting conservatism, (3) tax incentives on accounting conservatism, and (4) litigation risk on accounting conservatism. The type of research used is quantitative research. The population in this study are all manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2016-2020 which are known to be 54 companies and the sampling technique uses the purposive sampling method. Obtained a sample of 23 companies x 5 years = 115 financial statement data. In this study, the data used are secondary data and the analytical techniques used are the classical assumption test analysis method, multiple linear regression analysis, hypothesis testing and the coefficient of determination. The results obtained using multiple linear regression analysis concluded that capital intensity, financial distress, tax incentives and litigation risk partially have a significant effect on accounting conservatism in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2016-2020.Keywords: Capital Intensity, Financial Distress, Tax Incentives, Litigation Risk, and Accounting Conservatism.